Diversity of butterflies in four different forest types in Mount Slamet, Central Java, Indonesia - IMAM WIDHIONO (Biodiversitas Journal of Biological Diversity, 2015)
Widhiono I. 2015. Diversity of butterflies in four different forest types in Mount Slamet, Central Java, Indonesia.Biodiversitas 16: 196-204. The study was carried out in four different habitat types (secondary forest, plantation forest, agroforest, andtourist area) on the southern slope of Mount Slamet, Baturaden Forest, Central Java, Indonesia from July 2009 to August 2010. A totalof 99 species belonging to eight families showed a dominance of Nymphalidae (30 species) followed by Pieridae (17 species),Lycaenidae (15 species), Papilionidae (13 species), Satyridae (11 species), Danaidae (6 species), Amathusidae (4 species), andRiodinidae (3 species). From the 99 butterflies species found on the southern slope of Mount Slamet, 32 species (30%) were specific tothe forest, whereas 63 species (60.6%) were common to all habitats sampled, and the last 10 species (9.4%) were endemics species withone protected species (Troides helena). The present results was showed that butterflies diversity, abundance, and endemism is stillrelatively high, representing 18% of all butterfly species found in Java and supporting 71.4% endemic species found in Central Java.The plantation forest were contributed the highest diversity and abundance of butterfly species, whereas the agroforest showed thelowest diversity, abundance, and endemism. Among all habitats surveyed, the secondary forest represented the most suitable habitat forbiodiversity conservation and maintenance of rare and endemic species.